Reliable routing algorithm based on fuzzy logic for Mobile Ad Hoc Network - Ghalavand, Golnoosh; Dana, Arash; Ghalavand, Azadeh; Rezahosieni, Mahnaz (2010 3rd International Conference on Advanced Computer Theory and Engineering(ICACTE), 2010)
For unpredictable manner of mobile ad hoc network (manet), due to mobility of nodes in network, the shortest path is not necessarily the better path. If we do not consider the stability of routing path, then wireless links may be easily broken. Hence it is important to find a route that endures a longer time. Recently, efforts in this field have dealt the parameters battery power or trust of a node individually to find a reliable path. Our proposal combines these two parameters to discover a reliable route between the source and destination. In general, finding a path subject to multiple constraints is an NP-complete problem that cannot be exactly solved in polynomial time. Accordingly, In this paper, we propose a reliable routing algorithm based on fuzzy-logic (RRAF) for finding a reliable reactive protocol in Mobile Ad Hoc Networks. During route discovery, node with more trust value and maximum energy capacity is selected as a router based on a parameter called "Reliability Value". This approach forms a reliable route from source to destination thus increasing network life time and decreasing number of packet loss during transmission.